Whale catches from 19th century shore stations in Western Australia - Gibbs, Martin (J. Cetacean Res. Manage., 2023)
This paper presents historical data from 19th century shore whaling stations along the Western Australian coast, complementing data already presented in an earlier 1985 analysis. In particular, catch records of the Castle Rock whaling station, Geographe Bay, Western Australia, for the period 1846–53 together with other contemporary records indicate that humpback whales (Megaptera novaeangliae) comprised the majority of the colonial shore whalers’ catch. It is suggested that this could have been a result of a significant presence of American whale ships in the region in the early 1840s, which had presumably already reduced southern right whale (Eubalaena australis) numbers by the time these detailed colonial records were kept.